(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the care provided by health professionals to older adults with medical diagnosis of diabetes mellitus in primary health care services in the city of Bagé, Rio Grande do Sul. Method: Cross-sectional population-based study conducted in the urban area of Bagé, Rio Grande do Sul, with people aged 68 years or older belonging to the Siga-Bagé cohort study wave2016/17. The "adequate care" outcome was investigated considering the questions related to laboratory and physical tests performed in the year prior to the interview and the receipt of guidance about the reduction of sugar consumption. The descriptive analysis verified the proportional distribution of the outcome and the respective 95% confidence intervals (95%CI). Results: 735 older adults were interviewed. The most prevalent self-reported test was fasting glucose (93.2%; 95%CI: 89.1; 97.3), and diabetic foot examination (14.5%; 95%CI: 8.7; 20.3) was the one with the lowest prevalence. Regarding adequate care, only 1.4% (95%CI: -0.1; 3.3) of the elderly had all six indicators performed/evaluated. Conclusion: The prevalence of adequate care for diabetes was lower than expected and shows the fragility of health services in care. Healthcare should be comprehensive, longitudinal and coordinated by primary care services. It is important to manage correctly the chronic condition based on a Singular Therapeutic Project and the need for laboratory monitoring, with health guidelines focused on the individual, family and community.